2020
DOI: 10.1128/aem.02875-19
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Bifidobacterial Populations within the Canine and Feline Gut Microbiota

Abstract: During the course of evolution, dogs and cats have been subjected to extensive domestication, becoming the principal companion animals for humans. For this reason, their health care, including their intestinal microbiota, is considered of considerable importance. However, the canine and feline gut microbiota still represent a largely unexplored research area. In the present work, we profiled the microbiota of 23 feline fecal samples by 16S rRNA gene and bifidobacterial internally transcribed spacer (ITS) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Notably, a metagenomic study revealed that the Coriobacteriaceae family is the main representative of the Actinobacteria phylum, with Collinsella and Slackia as dominant genera in dogs, while Eggerthella and especially Olsenella being prevalent in cats (Handl et al ., 2011). Furthermore, recently, the application of the bifidobacterial ITS microbial profiling method to multiple canine and feline faecal samples revealed the presence of several Bifidobacterium species in each processed sample (Alessandri et al ., 2019a–c, 2020), thus strengthening the notion that bifidobacteria are ubiquitous commensal microorganisms of the intestinal microbial community of mammals, including dogs and cats (Milani et al ., 2017a,b).…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catssupporting
confidence: 52%
See 2 more Smart Citations
“…Notably, a metagenomic study revealed that the Coriobacteriaceae family is the main representative of the Actinobacteria phylum, with Collinsella and Slackia as dominant genera in dogs, while Eggerthella and especially Olsenella being prevalent in cats (Handl et al ., 2011). Furthermore, recently, the application of the bifidobacterial ITS microbial profiling method to multiple canine and feline faecal samples revealed the presence of several Bifidobacterium species in each processed sample (Alessandri et al ., 2019a–c, 2020), thus strengthening the notion that bifidobacteria are ubiquitous commensal microorganisms of the intestinal microbial community of mammals, including dogs and cats (Milani et al ., 2017a,b).…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catssupporting
confidence: 52%
“…The Clostridia class is represented by Clostridium clusters IV ( Ruminococcaceae family and Faecalibacterium prausnitzii ), XI ( Peptostreptococcaceae family) and XIVa ( Lachnospiraceae family and Blautia ), while the Erysipelotrichi is mainly represented by Turicibacter , Catenibacterium and Coprobacillus genera (Ritchie et al ., 2010; Handl et al ., 2011; Pilla and Suchodolski, 2019). Furthermore, Prevotella and Bacteroides , belonging to the Bacteroidetes phylum, are among the most abundant and prevalent bacterial genera of the faecal microbiota of both companion animals considered here (Alessandri et al ., 2019a–c, 2020).…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bacterial genera present in at least 70% of the studies and with a prevalence ranging from 30% to 70% were used to reconstruct the accessory-microbiota ( Tables S6, S7, S8 and S9 ). The cut-off values were chosen based on previous publications [50] , [51] and adapted to the high variability of the infant microbiota. Interestingly, the achieved results revealed that the core-microbiota (taxa with prevalence > 70%) of 0–1 M and 1–6 M groups was mostly represented by the Bifidobacterium genus (average abundance of 38.07% ± 34% and 44.16% ± 29.10%, respectively) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Research has often been directed to the intestinal microbiomes of ruminants [147][148][149][150][151][152][153] and other commercially valuable species [154][155][156]. By virtue of ease of access, other studies have tended to be on domesticated species [157], or wild species which can be more conveniently reached and investigated [158].…”
Section: Animal Adaptation To Aridity and Animal-associated Microbiomesmentioning
confidence: 99%